1985
DOI: 10.1136/gut.26.11.1189
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin inhibits gastric acid secretion after gastric mucosal prostaglandin synthesis inhibition by indomethacin in man.

Abstract: SUMMARY The inhibitory effect of indomethacin, 200+200 mg administered per os over 24 hours, on the prostaglandin E2 generative capacity of gastric mucosal tissue was determined in healthy male volunteers. The effect of prostaglandin synthesis inhibition on somatostatin induced suppression of food-stimulated acid secretion was tested. Peptone meal stimulated acid secretion was quantified in five healthy volunteers by intragastric titration with and without indomethacin pretreatment. Somatostatin doses of 200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In addition to suppressing gastrin release, somatostatin also directly inhibits the pari etal cell [48], Although two studies in the rat suggested that indomethacin interacted with the effect of infused somatostatin on the parietal cell [14,17], repeated efforts to re produce the results in man have been unsuc cessful [21,22], in agreement with the present observations. However, plasma gas trin was not monitored in the previous stud ies.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to suppressing gastrin release, somatostatin also directly inhibits the pari etal cell [48], Although two studies in the rat suggested that indomethacin interacted with the effect of infused somatostatin on the parietal cell [14,17], repeated efforts to re produce the results in man have been unsuc cessful [21,22], in agreement with the present observations. However, plasma gas trin was not monitored in the previous stud ies.…”
Section: Discussionsupporting
confidence: 81%
“…For example, gastric emptying in the dog has been observed to be delayed by somatostatin, but in humans, conflicting data have been reported. Johansson et al (1 11) observed that the early gastric emptying of an oral glucose meal is enhanced by somatostatin, and similar effects were noted by Mogard et al (152). In contrast, Johansson et al (112) have also reported in separate studies that the later phases of gastric emptying are delayed by the peptide.…”
Section: Gastrointestinal Motilitymentioning
confidence: 80%
“…Thus somatostatin may stimulate the release of some as yet unidentified final inhibitory mediator. Prostaglandins do not appear to play a crucial role because cyclo-oxygenase inhibition does not interfere with the inhibitory response (125). The possibility that an intestinal inhibitor distinct from secretin is released by acid from the duodenal bulb has been entertained.…”
Section: Acid-induced Inhibitionmentioning
confidence: 98%